Awareness of human papillomavirus among women attending a well woman clinic. Issue 4 (5th August 2003) - Waller, J; McCaffery, K; Forrest, S; Szarewski, A; Cadman, L; Wardle, J
Abstract : Objectives: To assess the level and accuracy of public understanding of human papillomavirus (HPV) in the United Kingdom. Methods: Women attending a well woman clinic were asked to complete a questionnaire assessing HPV awareness and specific knowledge about the virus. Results: Questionnaires were completed by 1032 women, of whom 30% had heard of HPV. Older women, non-smokers, and those with a history of candida, genital warts, or an abnormal smear result were more likely to have heard of HPV. Even among those who had heard of HPV, knowledge was generally poor, and fewer than half were aware of the link with cervical cancer. There was also confusion about whether condoms or oral contraceptives could protect against HPV infection. Conclusions: In this relatively well educated sample, awareness and knowledge of HPV were poor. Public education is urgently needed so that women participating in cervical cancer screening are fully informed about the meaning of their results, especially if HPV testing is soon to be introduced.